Coronary Computed Tomography Angiography for the Assessment of Acute Chest Pain in the Emergency Department. Issue 3 (May 2015) - Ropp, Alan; Lin, Cheng T.; White, Charles S.
<x xml:space="preserve">Abstract</x> Acute chest pain is an important clinical challenge and a major reason for presentation to the emergency department. Although multiple imaging techniques are available to assess such patients, considerable interest has focused on the use of coronary computed tomography (CT) angiography. Three recent multicenter trials have demonstrated the value of coronary CT angiography (CCTA) to diagnose patients with acute coronary syndrome (ACS) rapidly and accurately. Guidelines developed on the basis of these and other studies suggest that CCTA is optimally used in patients with low to intermediate risk for ACS. A related protocol, the triple rule-out scan, may be valuable if overlapping symptoms occur, particularly between those of ACS and pulmonary embolism. In developing a program to perform CCTA in the emergency room, it is important to work closely with emergency physicians and cardiologists to maximize appropriate use of this technique and to develop appropriate protocols that minimize radiation dose. Ongoing efforts to improve existing capabilities of CCTA include better characterization of coronary plaque and the use of CT fractional flow reserve and perfusion techniques.